2013
DOI: 10.1371/journal.pone.0075143
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrin-like Proteins in the Necrotrophic Fungus Alternaria brassicicola Have a Role in Plant Pathogenesis and Stress Response

Abstract: In this study, the roles of fungal dehydrin-like proteins in pathogenicity and protection against environmental stresses were investigated in the necrotrophic seed-borne fungus Alternaria brassicicola. Three proteins (called AbDhn1, AbDhn2 and AbDhn3), harbouring the asparagine-proline-arginine (DPR) signature pattern and sharing the characteristic features of fungal dehydrin-like proteins, were identified in the A. brassicicola genome. The expression of these genes was induced in response to various stresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Very often dormancy in seeds is concomitant with extreme drying begging the question of whether microbes require some level of desiccation tolerance to survive during seed dormancy. Some pioneer studies are indeed pointing to the capacity of some microorganisms to cope with stress conditions likely accompanying the seed maturation process as an essential component of efficient seed colonization (Pochon et al 2012(Pochon et al , 2013. What role do seed microbiota play in the assembly of the plant microbiota?…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Very often dormancy in seeds is concomitant with extreme drying begging the question of whether microbes require some level of desiccation tolerance to survive during seed dormancy. Some pioneer studies are indeed pointing to the capacity of some microorganisms to cope with stress conditions likely accompanying the seed maturation process as an essential component of efficient seed colonization (Pochon et al 2012(Pochon et al , 2013. What role do seed microbiota play in the assembly of the plant microbiota?…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…During host infection, A. brassicicola is exposed to high levels of defense compounds, such as phytoalexins and glucosinolate breakdown products, and the ability to overcome these antimicrobial metabolites is a key factor in determining fungal virulence (Pochon et al, 2013). The A. brassicicola genome size is approximately 31.9 Mb.…”
Section: A Brassicicolamentioning
confidence: 99%
“…We decided to use a mixture of pathogen isolates for screening of our collection of Brassicaceae cultigens, by selecting the isolates highest in aggressiveness as per the preliminary assays. Other scholars of this pathosystem have used isolates with contrasting pathogenicity towards the host plants (Cho et al 2006;Pochon et al 2013;Su'udi et al 2011). Alternatively, and similar to our approach, plants with varying reactions to the pathogen were used for experimentation (Doullah et al 2006;Mazumder et al 2013;Meena et al 2011;Sharma et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, we observed the defense responses in host plant leaves: A drastic reorganization of actin networks, deposition of papillae, cell death upon colonization, and limitation of pathogen spread by callose deposition around the infected cell(s). Some authors (Pochon et al 2013;Sharma et al 2014) reported on A. brassicicola infection routes (i.e., leaf penetration modes) depending on a given isolate aggressiveness but agreed on both direct (epidermal) and stomatal penetration possible for the Alternaria spp. in several pathosystems.…”
Section: Discussionmentioning
confidence: 99%